Determinants of the Quality Financial Information Small and Medium Enterprises Sector: SME s - Eddy sarwono, Aris; Asih Handayani (International Journal of Science, Technology & Management, 2021)
This study aims to determine the effect of owner support, personal technical skills, training and education programs, age, gender, length of business and formal education on the performance of accounting information systems. This research was conducted on Small and Medium Enterprises (SMEs) in the Solo Raya area. The type of data used is quantitative data. The data source used is primary data. Data collection techniques using a questionnaire. The population in this study is SMEs in the Solo Raya area. The sampling technique used purposive sampling method with the number of samples determined with a specific purpose as many as 56 SMEs. The results showed that the variables of owner support, personal technical ability, training and education programs had an effect on the performance of the accounting information system, while variables of age, gender, length of business and formal education had no effect on the performance of the accounting information system.